Exploring the Context Dependency of the PSM–Performance Relationship. (September 2018) - Lynggaard, Mikkel; Pedersen, Mogens Jin; Andersen, Lotte Bøgh
The public service motivation (PSM) of public employees matters to their performance at work. Yet research on how context factors moderate the PSM–performance relationship is sparse. This article shows how the PSM–performance relationship may depend on two context factors: (a) the extent of work autonomy that a public organization provides its employees and (b) the service users' capacity to affect the organization's service provision. We test a set of moderation hypotheses using school data (teacher survey data with administrative data on schools and student). Using within-student between-teachers fixed effects regression, we find a stronger PSM–performance relationship in organizational contexts involving greater regulation of employee work autonomy for users with low to moderate user capacity.